Catheter-Based Cardiovascular Interventions A Knowledge-Based Approach - Lanzer, Peter. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Operator skills, and in particular decision-making and strategic skills, are the most critical factor for the outcome of catheter-based cardiovascular interventions. Currently, such skills are commonly developed by the empirical trial and error method only. In this textbook, for the first time, an explicit teaching, training, and learning approach is set out that will enable interventional operators, whether cardiologists, vascular surgeons, vascular specialists, or radiologists, to learn about and to develop the cognitive skills required in order to achieve consistent expert-level catheter-based interventions. It is anticipated that adoption of this approach will allow catheter-based interventions to become a domain of excellence, with rapid transfer of knowledge, steep learning curves, and highly efficient acquisition of complex skills by individual operators all of which are essential if we are to meet successfully the challenges of modern cardiovascular care embedded in highly competitive health care markets.